Constructive side-channel analysis and secure design : 8th International Workshop, COSADE 2017, Paris, France, April 13-14, 2017, Revised selected papers /: 8th International Workshop, COSADE 2017, Paris, France, April 13-14, 2017, Revised selected papers. ([2017]) - Unknown
No abstract available